Manajemen Risiko Pada Penjualan UMKM Di Dukuh Wonorejo Berbasis Digitalisasi - Setiadi, Ikhbal Tria; Al Rizqi, Muhammad Rana; Amelita, Arvira; Sari, Dewi Sekar; Malik, Elanisa; Akbar, Muhammad Ilham; Raiz, Muhammad Faizal; Hidayat, Sholeh Nur; Andayani, Saraswati Surya Ning; Jaya, Heromadhan Ilham Syaputra; Rachmawati, Putri (Universitas Muhammadiyah Yogyakarta, 2025)
Wonorejo Hamlet has great potential in the development of Small and Medium Enterprises (SMEs) and cultural-based tourism. However, limitations in business risk management and the minimal use of digital technology are the main barriers to local economic development. The aim of this community service is to enhance product sales of SMEs, promote village tourism through digitalization, and provide risk management training to SMEs in Wonorejo Hamlet. Training was provided to SME actors to equip them with risk mitigation strategies, while the village digitalization was realized through the creation of promotional content published on Instagram and YouTube. The methods used in this activity include observation, interviews, Focus Group Discussions (FGD), risk management training, and the implementation of village digitalization through social media. The results of the program show an increase in the understanding and skills of the community in managing risk, where 85% of respondents have understood the basic concepts and their application in business. The village digitalization program also received positive feedback, with 94.7% of respondents wanting the program to continue. Digitalization has proven to help expand the marketing reach of SMEs and introduce Wonorejo Hamlet to the wider community. With this program, the community is better prepared to manage businesses sustainably and can effectively utilize digital technology as a promotional tool. The sustainability of the program is expected to further drive local economic progress and introduce the potential of Wonorejo Hamlet to a broader audience